Suicidal Ideation, Self-esteem, and Hopelessness in Patients With Pulmonary Arterial Hypertension - Korkmaz, Sevda; Akbulut, Mehmet; Kazgan, Aslı; Hekim, Alaattin; Yıldız, Sevler; Özsoy, Filiz; Korkmaz, Hasan (Physicians Postgraduate Press Inc., 2021)
Objective: To investigate the frequency of suicidal ideation and its correlation with other clinical variables in patients with pulmonary arterial hypertension. Methods: Fifty patients with pulmonary arterial hypertension who presented to the cardiology department between 2018 and 2019 and 50 healthy controls were included in the study. A sociodemographic and clinical data form was completed by both the patients and controls, and the Beck Depression Inventory (BDI), Beck Hopelessness Scale (BHS), Rosenberg Self-Esteem Scale (RSE), and Suicide Probability Scale (SPS) were administered. SPSS version 22 software was used in the statistical analysis. Results: The mean ± SD systolic pulmonary pressure of the patients was 47.48 ± 18.86 and the pulmonary artery pressure was 33.32 ± 19.69. BHS, BDI, and SPS total scores were statistically significantly higher in the patient group compared to the control group (P < .001, P = .001, P = .026, respectively). RSE scores were also higher in the patient group compared to the control group (P = .017). Conclusions: It is important to identify pulmonary arterial hypertension patients with intense feelings of hopelessness and depressive symptoms and to provide psychiatric treatment and psychotherapeutic interventions to improve their self-esteem. © 2021 Physicians Postgraduate Press, Inc.
Keywords: Humans; Psychiatric Status Rating Scales; Pulmonary Arterial Hypertension; Self Concept; Suicidal Ideation; Suicide; adult; Article; Beck Depression Inventory; Beck Hopelessness Scale; clinical article; controlled study; cross-sectional study; depression; educational status; employment status; exhaustion; female; heart ventricle size; hopelessness; hostility; household income; human; Likert scale; lung artery pressure; male; mental disease assessment; pessimism; psychiatric treatment; pulmonary artery systolic pressure; pulmonary hypertension; Rosenberg Self-Esteem Scale; self esteem; self evaluation; smoking; suicidal ideation; suicide probability scale; psychological rating scale; self concept; suicidal ideation; suicide